The Eye in Pediatric Systemic Disease - Levin, Alex V.; Enzenauer, Robert W. (Springer International Publishing : Imprint: Springer, 2017)
This book is the first of its kind to describe ocular manifestations of systemic diseases in the pediatric population. Written and edited by experts in areas of pediatric ophthalmology and genetics, this new text covers a multitude of topics in a comprehensive and cataloged fashion. The Eye in Pediatric Systemic Disease is designed as an in-depth and up-to-date reference work that is heavily referenced, thus allowing the reader ready access to the international supporting literature. Everything from ocular manifestations of hematologic disease, child abuse, psychiatric diseases, renal disorders, and vitamin disorders are covered, allowing readers to know what to look for in the eyes of children with a given systemic disorder. The Eye in Pediatric Systemic Disease is written in language that is accessible to ophthalmologists and pediatricians, as well as allied health care professionals.- Resumé vydavatel
Keywords: dětská oftalmologie; oční nemoci; děti; pediatric ophthalmology; eye diseases; children; elektronické knihy; kolektivní monografie; electronic books; collective monographs